Sufism Healing Method for Drugs Rehabilitation: A Case Study in PP. Suryalaya Tasikmalaya, West Java, Indonesia - ihsan kamaludin; Maya Najihatul Ula (Ulumuna, 2019)
Sufism activities cover not only rituals but also pseudo-medical treatment. This can be seen from the daily routines of Sufi order (tarekat) of Qadiriah wa Naqsabandiah (TQN) at the Pesantren Suryalaya, Tasikmalaya, West Java. Known as a center of Islamic learning, the pesantren also offers spiritual treatments to cure victims of drug abuse. This study aims to explore this Sufis practices of healing method. Based on an ethnographic study in this locale, the study specifically analyses the method of treatment called inābah. This is a unique technique employed by the Sufis to cure the patients of drug abuse. This study shows that the Sufi masters provides a spiritual and technical guidance in the treatment processes to stimulate drug victims’ awareness through a series of spiritual and pseudo-medical processes. In the view of the Sufis, drug abuse can be cured by means of increasing spiritual activities, such as chanting and praying. Moreover, this method also requires embodied practice of repentance by, for example, fasting, bathing and other related ritual processes determined by the Sufi masters. The processes by which the victim take thus include both spiritual and corporal requirements since illness or disease is seen both as a result of spiritual and physical transgressions.